Ca2+ store dynamics determines the pattern of activation of the store-operated Ca2+ current I(CRAC) in response to InsP3 in rat basophilic leukaemia cells. - Glitsch, M; Parekh, AB (2000)
1. The relationship between the amplitude of the store-operated Ca2+ ICR AC and intracellular inositol 1,4,5-triphosphate (InsP3) concentration is complex. In rat basophilic leukaemia (RBL-1) cells dialysed with high intracellular Ca2+ buffer, the relationship is supra-linear with a Hill coefficient of 12 and resembles an apparent 'all-or-none' phenomenon. The non-linearity seems to arise from InsP3 metabolism. However, it is not clear which InsP3-metabolising pathway engenders the non-linear behaviour nor whether ICRAC is always activated to its maximal extent by InsP3. 2. Using the whole-cell patch clamp technique, we dialysed RBL-1 cells with different concentrations of the InsP3 analogue InsP3-F. InsP3-F is broken down by Ins(1,4,5)P3 5-phosphatase but is not a substrate for Ins(1,4,5)P3 3-kinase. The relationship between InsP3-F and ICRAC amplitude was supra-linear and very similar to that with InsP3 but was distinct from the graded relationship seen with the non-metabolisable analogue Ins2,4,5P3. 3. In the presence of high intracellular Ca2+ buffer, InsP3-F activated ICRAC to its maximal extent. With moderate Ca2+ buffer, however, sub-maximal ICRAC could be obtained to a maximal InsP3-F concentration. Nevertheless, the relationship between the amplitude of ICRAC and InsP3-F concentration was still supra-linear. 4. Submaximal ICRAC in response to InsP3-F in the presence of moderate Ca2+ buffer was due to partial depletion of the stores, because the size of the current could be increased by thapsigargin. 5. The data suggest that first Ins(1,4,5)P3 5-phosphatase is an important factor which contributes to the non-linear relationship between InsP3 concentration and the amplitude of ICRAC and second, InsP3 does not always activate ICRAC to its maximal extent. At moderate buffer strengths, submaximal ICRAC is evoked by maximal InsP3. However, the supra-linear relationship between InsP3 concentration and amplitude of the current still holds.